Donor-Related Risk Factors for Graft Decompensation Following Descemet's Stripping Automated Endothelial Keratoplasty - Nishisako, Sota; Yamaguchi, Takefumi; Hirayama, Masatoshi; Higa, Kazunari; Aoki, Dai; Sasaki, Chiaki; Noma, Hisashi; Shimazaki, Jun (Frontiers in Medicine, 2022)
Aims: To identify donor-related risk factors associated with graft endothelial failure and postoperative endothelial cell density (ECD) reduction after Descemet’s stripping automated endothelial keratoplasty (DSAEK). Methods: This was a single-center retrospective study conducted from July 2006-December 2016. We included 584 consecutive eyes (482 patients) that underwent DSAEK for the treatment of laser iridotomy-related bullous keratopathy (192 eyes), pseudophakic bullous keratopathy (137 eyes), regraft (96 eyes), Fuchs’ endothelial corneal dystrophy (FECD; 59 eyes) and others (100 eyes). Twenty-three donor- and recipient-related risk factors potentially associated with graft failure and ECD reduction were assessed using Cox hazard models and linear mixed effect models. Results: The median age of the patients was 73.5 years (male; 35.6%). After DSAEK, ECD decreased from 2674 cells/mm2 (95% confidence interval [CI]; 2646-2701) to 1132 (1076-1190) at 12 months and 904 (845-963) at 24 months (P < .001). Fifty-five eyes (9.4%) had graft endothelial failure without rejection. This failure was associated with donor pseudophakic lens status (hazard ratio [HR]; 2.67, CI; 1.50-4.76, P = .001) and preoperative endothelial folds (HR; 2.82, CI; 1.20-6.62, P = .02). The incidence of graft endothelial failure in non-FECD patients was significantly higher among those receiving donor grafts with a pseudophakic lens status and preoperative presence of endothelial folds (P < .001). Postoperative ECD loss was significantly greater in eyes with these risk factors compared to those without (P = .007). Conclusions: Pseudophakic status and/or presence of preoperative endothelial folds are the significant donor risk factors for endothelial failure in non-FECD patients.